Family Support and Glucose Control Related to Microvascular Complications Symptoms - Alfiah Kusuma Wardani; Muhammad Atoillah Isfandiari (Jurnal Berkala Epidemiologi, 2014)
Diabetes Mellitus (DM) is a chronic disease whose prevalence continues to increase. WHO predicts that DM will be 7 major diseases that will cause death in 2030. Many people don’t realize early that they have DM, so they suffer complications. An increase in the number of people with DM who experience complications can be caused by poor blood sugar control and a lack of support from the family. The complication that was observed in this study is micro-vascular complications. This study aims to analyze family support and control blood sugar levels with the incidence of micro-vascular complications in patients with DM in the Public Health Center (PHC) of Jagir Surabaya. This research uses an analytic observational study sample of patients who had DM not less than 5 years as many as 34 samples. The sampling was done by simple random sampling, while the data analysis uses the chi-square test. The results showed that there was no relationship between family support with symptoms of micro-vascular complications (p=0.069),but there is a relationship between the control of blood sugar levels with symptoms of micro-vascular complications (p=0.002). The micro-vascular symptoms that are often experienced by people with DM in the PHC of Jagir is symptomatic neuropathy complications. The proportion of patients with DM who received family support at 55.9%, while the patients with DM who control the blood sugar levels well were 17 respondents. It is expected that people with DM to control eating diet and regular exercise.